Pengaruh Model Direct Instruction Berbantuan LKPD terhadap Kemampuan Literasi Statistis Kelas V SDN 13 Pontianak Utara - Hermansyah, Rahmi; Tomo, Tomo; Hairida, Hairida (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study examines the effectiveness of the Direct Instruction learning model, enhanced by LKP, on statistical literacy skills in statistics among fifth-grade students at SDN 13 Pontianak Utara. An experimental design with a quasi-experimental approach was employed, involving a sample of 47 fifth-grade students. Data collection utilized test questions, which were analyzed using descriptive statistics and an independent samples t-test with SPSS version 22. The impact of the Direct Instruction model on students' statistical literacy was assessed using the effect size formula. The findings reveal that: (1) the learning process utilizing the Direct Instruction model supported by LKPD was implemented as intended and adhered to the established materials, (2) a significant difference exists in statistical literacy skills between students who engaged with the Direct Instruction model supported by LKPD and those who did not, and (3) the effect of this instructional model on statistical literacy skills is considered substantial, with an effect size of0.91.